The problem of Jews and Gentiles in the macro-structure of Romans - Boers, H. (Neotestamentica, 1981)
This can be considered another 'chapter' in my attempt to understand Romans. Some of the earlier work is left behind, but new steps are taken to understand the meaning of chapters 1 and 2 also, and of the paraenetic section, chapter 12-15, and so to bring the investigation of the macro-structure or semantic deep structure of the letter to a preliminary conclusion.